Morpho-cultural, biochemical analysis and molecular characterization of pigment producing Cordyceps militaris - Kuamr, Satish; Kaundal, Kirti; Rao, Anil; Sharma, Shweta; Sharma, Ved Parkash (Mushroom Research, 2023)
The study was conducted to ascertain the cultural growth and nutritional content of the strain Cordyceps militaris cultivated in India. Abundant mycelial density and darkest orange pigment was observed in Potato dextrose agar which was followed by Oat meal agarand least was observed in Yeast agar medium.Inbioactive compounds, adenosine and cordycepin content was1.8 mg/g and 9.8 mg/g respectively. Additionally, proximate analysis of Cordyceps militaris contained proteins (32gm/100g) and carbohydrate (40mg/100g), dietary fiber (1.97g/100g), fat (0.23g/100g), sodium (46mg/100g, vitamin C (113mg/100g), total ash (7.82gm/100g),and saturated fatty acid (0.12g/100g) on dry weight basis.Heavy metal analysis showed lesser amount of Pb, Cd (